Перехідна реологічна поведінка концентрованих суспензій каолініту - Булавін, Л.А.; Бойко, Ю.П.; Карпенко, О.Б.; Лебовка, М.І.; Храпатий, С.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The transient rheological behaviour of thixotropic aqueous suspensions of kaolinite has been investigated at the volume concentration φ = 13.7%. We found that their behaviour depends on pH (4.5 and 7.5) for the velocity range γ· = 1.5 ÷ 1030 s–1. The character of oscillatory rheological behaviour at γ· = 1 ÷ 10 s–1 essentially depends on the preliminary long-time rheological processing at γ· = 1030 s–1. To explain the oscillatory rheological behaviour, a cluster model has been proposed. The dependence of the cluster destroying probability on hydrodynamic shearing perturbations is taken into account.